Aetiological Evaluation of Patients with Meningitis in a Tertiary Care Hospital of Bangladesh (Bangladesh Medical Journal, 2019)
Meningitis is a global health problem as mortality is high and a large proportion of survivors suffered from significant morbidity. The physicians are facing this challenge of emergency identification of this clinical syndrome, establishing its etiology and its prompt treatment not only to ensure survival but also to prevent long term sequelae in these patients. Poor outcomes caused by bacterial meningitis due to delays in diagnosis and treatment. In Bangladesh, the epidemiological study regarding meningitis in adults is rare. Rapid & easily available as well as specific test or means are also not in our hand. The aim of this study was to evaluate the aetiology of patient with meningitis in tertiary care hospital of Bangladesh.The main objective was to evaluate the aetiology of meningitis of patients admitted in medical wards of a tertiary care hospital. The study was a descriptive type of observational study. The study was carried out in the Department of Medicine, Dhaka Medical College Hospital, a tertiary level hospital of Bangladesh from first July 2013 to thirty first December 2013. A total 50 patients were enrolled with Meningitis, diagnosed on clinical, biochemical, other investigational background , fulfilling the inclusion and exclusion criteria. Patients having feature of meningitis was enrolled in the study after getting informed written consent from patient or attendant. Detail demographic data were collected from the informant was recorded in structured case report form. Clinical examination and relevant investigation with CSF study were done. Routine follow up of the patient was done. Data analysis was conducted with SPSS software. Among the 50 patient the mostly affected groups were below 40 years of age comprising 66%. The mean(±SD) age was 33.04 ±18 years. There was an overall male preponderance with a male to female ratio 1.63:1 (N=31 vs N=19). The highest number of patients were presented with fever (100%), headache (98%) and altered mental status (88%). Among all 50 cases of meningitis 27(54%) were diagnosed as pyogenic, 9 (18%) were tuberculous meningitis and 14(28%) were viral . Out of 27 pyogenic meningitis cases 19 (70.37%) developed convulsion, out of 9 tuberculous meningitis 3 (33.33%) developed convulsion and 11 (78.57%) out of 14 viral cases had convulsion, that is convulsion was more common in viral cases. Sixteen male patients (51.61%) and 11 female patients (57.89%) had pyogenic meningitis, 5 male patients (16.12%) and 4 female patients (21.05%) had tuberculous meningitis. On the other hand, 10 (32.25%) male and 4 (21.05%) female had viral meningitis. P value was 0.369, So the male and female difference was not statistically significant. Diagnosis was made on the basis of clinical findings and CSF study. Pyogenic were more common than viral cases and tubercular meningitis. Meningitis is foremost causes of morbidity and mortality. It is recommended that provision of proper health care support, Proper and rapid detection and others investigation facilities reduce the disability. In the interim, this study provides data that can inform public health strategies directed at assessing and reducing meningitis severity and meningitis events.Bangladesh Med J. 2017 May; 46 (2): 26-31